Perakitan dan perbaikan komputer untuk meningkatan kualitas remaja di Desa Pandau Jaya Kecamatan Siak Hulu Kabupaten Kampar - Alfirman Alfirman; Sukamto Sukamto; Gita Sastria; Zaiful Bahri (Unri Conference Series: Community Engagement, 2019)
The objectives to be achieved in community service activities are, so that the participating communities can: 1). Having knowledge of how to basic assembly of computers, 2). Having knowledge about how to install a Windows operating system and its application programs, 3). Having knowledge about how to repair / boot booting on computer hardware or software. This community service is carried out based on our observation, that in Pandau Jaya Village, Siak Hulu District 80% of the community has no knowledge of assembly and maintenance on PC computers (personal computers) or laptops. With the development of technology, especially computers that are increasingly widespread, so as to provide employment opportunities in the field of computers will also be more wide open. For this reason, competence in how to assemble and repair computer hardware and software in the community, especially the people in Pandau Jaya Village, is highly needed so that they can later overcome the problems themselves on the computer equipment. The level of achievement of Community Service activities that have been carried out in Pandau Jaya village are: 1) community members, especially teenagers in Pandau Jaya village, Siak Hulu sub-district have knowledge and skills about basic assembly on computers. 2) Having knowledge and skills on how to make improvements to the computer. 3) Can overcome the interference if there are simple problems that arise at any time. 4) Having knowledge and skills on how to install an windows operating system along with application programs.